CONSTRUCTION A CORING FROM TENSOR PRODUCT OF BIALGEBRA - Prima Puspita, Nikken; Khabibah, Siti (PYTHAGORAS Jurnal Matematika dan Pendidikan Matematika, 2012)
In this Paper introduced a coring from tensor product of bialgebra. An algebra with compatible coalgebrastructure are known as bialgebra. For any bialgebra B we can obtained tensor product between B anditself. Defined a right and left B -action on the tensor product of bialgebra B such that we have tensorproduct of B and itself is a bimodule over B. In this note we expect that the tensor product B anditself becomes a B -coring with comultiplication and counit.Keywords : action, algebra, coalgebra, coring.